(untitled) (Global Journal of Science Frontier Research, 2016)
The aim of the present study is to investigate the bioactive compounds from the leaf extract of Mallotus oppositifolius using GCMS analysis. The chromatogram showed nine peaks indicating the presence of nine compounds in the extract. The major phytocompounds in the leaf were Glutaconic anhydride with the highest concentration in the extract, 40.19 peak area %, RT 22.686 and molecular formula C 5 H 4 O 3 ; 2-Mercaptophenol with 18.23 peak area %, RT 22.068 and molecular formula C 6 H 6 OS. Iso-Valreic and Valeric acids with 12.39,2.53 peak area %, RT 3.676,7.037 and the same molecular formula C 5 H 10 O 2 which had been proposed to have anticonvulsant effect in valerian and act as neurotransmitter. Oleamide with the least concentration of 2.15 peak area %, RT 27.959 and molecular formula C 18 H 35 NO which could induce sleep in animals, being studied as a potential medical remedy for mood and sleep disorder and cannabinoid-regulated disorder. The phytochemicals in Mallotus oppositifolius could be of therapeutic importance.